Aesthetic and Functional Rehabilitation of the Primary Dentition Affected by Amelogenesis Imperfecta - Maria Carolina Salomé Marquezin; Bruna Raquel Zancopé; Larissa Ferreira Pacheco; Maria Beatriz Duarte Gavião; Fernanda Miori Pascon (Case Reports in Dentistry)
The objective of this case report was to describe the oral rehabilitation of a five-year-old boy patient diagnosed with amelogenesis imperfecta (AI) in the primary dentition. AI is a group of hereditary disorders that affects the enamel structure. The patient was brought to the dental clinic complaining of tooth hypersensitivity during meals. The medical history and clinical examination were used to arrive at the diagnosis of AI. The treatment was oral rehabilitation of the primary molars with stainless steel crowns and resin-filled celluloid forms. The main objectives of the selected treatment were to enhance the esthetics, restore masticatory function, and eliminate the teeth sensitivity. The child was monitored in the pediatric dentistry clinic at four-month intervals until the mixed dentition stage. Treatment not only restored function and esthetic, but also showed a positive psychological impact and thereby improved perceived quality of life. The preventive, psychological, and curative measures of a young child with AI were successful. This result can encourage the clinicians to seek a cost-effective technique such as stainless steel crowns, and resin-filled celluloid forms to reestablish the oral functions and improve the child’s psychosocial development.